2006
DOI: 10.1128/jb.188.3.874-881.2006
|View full text |Cite
|
Sign up to set email alerts
|

The yjeB ( nsrR ) Gene of Escherichia coli Encodes a Nitric Oxide-Sensitive Transcriptional Regulator

Abstract: Microarray studies of the Escherichia coli response to nitric oxide and nitrosative stress have suggested that additional transcriptional regulators of this response remain to be characterized. We identify here the product of the yjeB gene as a negative regulator of the transcription of the ytfE, hmpA and ygbA genes, all of which are known to be upregulated by nitrosative stress. Transcriptional fusions to the promoters of these genes were expressed constitutively in a yjeB mutant, indicating that all three ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
235
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(242 citation statements)
references
References 45 publications
5
235
0
Order By: Relevance
“…The regulation of hmp transcription is complex involving several regulators including Fnr [12] and MetR [13]. Recently, it was discovered that the regulator NsrR represses hmp transcription in the absence of NO or nitrite [14,15]. NsrR is proposed to contain a NO-labile [Fe-S] cluster responsible for the NO-sensing capacity [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of hmp transcription is complex involving several regulators including Fnr [12] and MetR [13]. Recently, it was discovered that the regulator NsrR represses hmp transcription in the absence of NO or nitrite [14,15]. NsrR is proposed to contain a NO-labile [Fe-S] cluster responsible for the NO-sensing capacity [14].…”
mentioning
confidence: 99%
“…Recently, it was discovered that the regulator NsrR represses hmp transcription in the absence of NO or nitrite [14,15]. NsrR is proposed to contain a NO-labile [Fe-S] cluster responsible for the NO-sensing capacity [14]. The importance of Hmp as a mechanism of protection from endogenous hostderived NO has so far been shown in human macrophages challenged with Salmonella enterica and non-pathogenic E. coli [16,17,18].…”
mentioning
confidence: 99%
“…Additionally, NO can freely diffuse across membranes, whereas, GSNO susceptibility has been shown to be dependent on the Dpp dipeptide ABC transporter in Salmonella (12)(13)(14). As the first step for studying RNS challenge in E. coli, previous investigations often did not distinguish between RSNO and NO-mediated effects (15,16) and RSNOs were sometimes used as NO donors (17). Such studies set the foundation for further distinction between RSNO and NO.…”
mentioning
confidence: 99%
“…coli possesses a NO-specific response network: the transcription factors (TFs) NorR and NsrR mediate increased expression of defense proteins NO reductase NorV and NO dioxygenase HmpA, respectively, in response to NO (17,19,20). Using a systems analysis (21), we have shown that, consistent with the known chemistry, NO primarily affects E. coli by reacting with metal groups, including those in the cytochrome oxidases, the Fe-S clusters of IscR, and branched chain amino acid (BCAA) synthesis protein dihydroxy acid dehydratase (IlvD).…”
mentioning
confidence: 99%
“…The cluster is likely to be [4Fe-4S], and reaction with NO is accompanied by a decrease in DNA binding affinity and de-repression of NsrR-regulated promoters (Bodenmiller & Spiro, 2006;Tucker et al, 2008;Yukl et al, 2008;Crack et al, 2015). The previously characterized NsrR regulon includes genes encoding the NO-scavenging flavohaemoglobin (hmp), the RIC (repair of iron centres) protein that participates in the repair of NO-damaged [Fe-S] clusters (ytfE), the respiratory nitrite reductase Nrf that is also an NO reductase (nrfABCDEFG), genes involved in motility ( fliA) and aromatic amine metabolism (tynA, feaB), and genes of unknown function, for example ygbA, yccM and yeaR-yoaG (Bodenmiller & Spiro, 2006;Filenko et al, 2007;Lin et al, 2007;Rankin et al, 2008;Partridge et al, 2009). The NsrR binding site is an 11-1-11 bp inverted repeat of the consensus motif AAGATGCYTTT (Bodenmiller & Spiro, 2006).…”
Section: Introductionmentioning
confidence: 99%